2013
DOI: 10.1371/journal.pone.0077786
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids are Key in 4-Hydroxy-2-Nonenal-Mediated Activation of Uncoupling Proteins 1 and 2

Abstract: The production of reactive oxygen species (ROS) in mitochondria is very sensitive to the proton motive force and may be decreased by mild uncoupling, mediated e.g. by mitochondrial uncoupling proteins (UCPs). UCPs were conversely hypothesized to be activated by ROS. Conclusions from experiments studying the reactive product of lipid peroxidation 4-hydroxy-2-nonenal (HNE) in isolated mitochondria and UCP knock-out mice are highly controversial. Here we investigated the molecular mechanism of HNE action by evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 48 publications
1
28
1
Order By: Relevance
“…10 A). This supports our previous results that modification of these amino acids in UCP1 does not affect its activity (51,55).…”
Section: The Inhibition Mechanism Of Ucps By Genipin At Low Concentrasupporting
confidence: 93%
See 1 more Smart Citation
“…10 A). This supports our previous results that modification of these amino acids in UCP1 does not affect its activity (51,55).…”
Section: The Inhibition Mechanism Of Ucps By Genipin At Low Concentrasupporting
confidence: 93%
“…Further, we used NHS, MNBS, and NEM to block the lysine, histidine, and cysteine residues of UCP1, respectively (51). As the unmodified control, UCP1 was incubated with an equal volume of water.…”
Section: Genipin At Low Concentrations Inhibits Ucp1 By Binding To Armentioning
confidence: 99%
“…This synergistic effect on UCP1 activity was also found in studies of UCP1 in planar lipid bilayers. Again, 4-HNE alone had no effect on UCP1 activation but strongly potentiated membrane conductance mediated by fatty acids (57). Interestingly, these effects coincided with cysteine modification of UCP1 by 4-HNE, whereas pre-treatment of UCP1 with cysteine-alkylating agents could inhibit 4-HNEdependent potentiation (57).…”
Section: Minireview: Ros and Adipose Tissue Thermogenesis Ated Hmentioning
confidence: 91%
“…In subsequent studies, a high membrane potential was suggested as a requirement for the activation of UCP-mediated uncoupling by HNE [47]. Experiments performed in a well-defined system of bilayer membranes reconstituted with recombinant UCPs [48] revealed that HNE did not directly activate either UCP1 or UCP2. However, HNE strongly potentiated the membrane proton conductance increase mediated by different long-chain FAs in UCP-containing and UCP-free membranes.…”
Section: Ros Detoxification Systemsmentioning
confidence: 99%